2019
DOI: 10.1021/acsomega.8b03517
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Molecular Construction: Driving the Self-Assembly by Coordination and Hydrogen Bonds Using 6-(Pyridin-2-yl)-1,3,5-triazine-2,4-diamine with M(NO3)2 Salts

Abstract: A new series of hydrogen-bonded metallotecton networks 6–9 of the general formula [M( 2 ) 2 (NO 3 ) 2 ] were obtained from the reaction of 6-pyridin-2-yl-[1,3,5]-triazine-2,4-diamine 2 with transition-metal ions [M: Co(II), Ni(II), Cu(II), and Zn(II)]. Their supramolecular networks and associated properties were characterized by single-crystal and powder X-ray diffraction, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It is noteworthy that motif IV has already been reported for association of DAT groups in our previous work. 36,46 The network is reinforced by multiple hydrogen bonds involving ClO 4 − . Summaries of the crystallographic data and hydrogen bonds and angles are provided in Table S1 and Table S2.…”
Section: ■ Structural Studymentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that motif IV has already been reported for association of DAT groups in our previous work. 36,46 The network is reinforced by multiple hydrogen bonds involving ClO 4 − . Summaries of the crystallographic data and hydrogen bonds and angles are provided in Table S1 and Table S2.…”
Section: ■ Structural Studymentioning
confidence: 99%
“…In crystal engineering, 1 is called a tectoligand 35 and 2 and 3 metallotectons. 36,37 They are compounds that can self-assemble to form robust framework hydrogen bonds with reliable patterns. The presence of -NH 2 Lewis basic sites and triazinyl rings (πelectron deficient core) makes them particularly good candidates for the photocatalytic CRR.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have demonstrated the coordination nanostructures by altering organic ligands, such as carboxylate, 3,5,12,18 hydroxyl, 14,20,21 pyridine, 9,22-25 and triazine. [26][27][28][29][30] The triazine derivatives are important in a range of areas as ligands for supramolecular self-assembly of more complex mixed layers, hence it may be interesting to study the coordination properties of the triazine derivatives. In this article, we fabricated different coordination nanostructures by 4,4 0 ,4 00 -(1,3,5-triazine-2,4,6-triyl) tribenzoic acid (TATB) molecules coordinating with Cu 2+ or Fe 3+ ion with different concentrations on highly oriented pyrolytic graphite (HOPG) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes based on coordination of both unsubstituted and functionalized bipyridine (bpy), terpyridine (tpy) and quaterpyridine (qtpy) with transition metals have been widely studied in particular for the formation of various metallosupramolecular architectures. [1][2][3][4][5][6][7][8] There is very extensive literature concerning polypyridine ligands and their complexes, but a relatively few investigations have been done on functionalized systems, particularly on qtpy. Many interests were focused on qtpy, a tetradentate ligand that can form metal complexes of different geometries.…”
Section: Introductionmentioning
confidence: 99%